2022
DOI: 10.1186/s12967-022-03537-x
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Helicobacter pylori, fibroblasts, and cancer cells induces fibroblast activation and serpin E1 expression by cancer cells to promote gastric tumorigenesis

Abstract: Background Helicobacter pylori (H. pylori) can disrupt the tight junctions between gastric epithelial cells and penetrate the intercellular spaces acting on epithelial cells, normal fibroblasts (NFs), and cancer-associated fibroblasts (CAFs), but their interaction in gastric cancer tumorigenesis and progression remains unclear. Methods Primary CAFs and NFs were isolated from paired gastric cancer tissues and adjacent normal tissues and identified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Human GC cell line (MKN45) and the umbilical vein endothelial cells (HUVECs) were purchased from the Shanghai Cell Bank of the Chinese Academy of Sciences (Shanghai, China). Three primary CAFs and GC cells from the same patients with GC were previously isolated from resected GC tissues [ 16 ]. All cells and strains were tested to eliminate the possibility of mycoplasma contamination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human GC cell line (MKN45) and the umbilical vein endothelial cells (HUVECs) were purchased from the Shanghai Cell Bank of the Chinese Academy of Sciences (Shanghai, China). Three primary CAFs and GC cells from the same patients with GC were previously isolated from resected GC tissues [ 16 ]. All cells and strains were tested to eliminate the possibility of mycoplasma contamination.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, infection with H. pylori elevated the expression of VCAM1 in CAFs to promote GC cell invasion via the JAK/STAT1 pathway [ 15 ]. In our recent study [ 16 ], we reported that the association among H. pylori , normal fibroblasts, and GC cells induced the activation of fibroblast into CAFs and upregulation of Serpin family E member 1 (Serpin E1) by GC cells, thereby promoting gastric carcinogenesis. However, it remains unclear whether Serpin E1 is produced by fibroblasts or cancer cells in the inflammatory microenvironment induced by H. pylori , and the underlying mechanism by which Serpin E1 promotes GC development remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The human GC cell lines AGS, NCI-N87 and SNU-16 cells were purchased from ATCC, and SGC-7901 and BGC823 cells were obtained from the tissue bank in Shanghai, China. Primary GC cells were separated and identified in our laboratory[ 25 ]. All cell lines were grown in 5% CO2 at 37 °C in RPMI-1640 with 10% FCS (Gibco, United States).…”
Section: Methodsmentioning
confidence: 99%
“…Gerbil stomachs, nude mouse xenografts, and human GC tissues were cut into 5-μm thick sections. Immunohistochemistry was used to detect expression of JUN, DKK1, CKAP4 and Ki67 in these tissues, and immunofluorescence imaging was used to assess β-catenin expression and nuclear translocation in DKK1-silenced AGS cells, as described previously[ 25 ]. The quantification of immunohistochemical staining was performed by Image J software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation